-7y+3=

Simple and best practice solution for -7y+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7y+3= equation:


Simplifying
-7y + 3 = 0

Reorder the terms:
3 + -7y = 0

Solving
3 + -7y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -7y = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -7y = 0 + -3
-7y = 0 + -3

Combine like terms: 0 + -3 = -3
-7y = -3

Divide each side by '-7'.
y = 0.4285714286

Simplifying
y = 0.4285714286

See similar equations:

| 6x-y=-23 | | -2u=-2/9 | | -6(-3y+6)-4y=5(y-8)-2 | | 7-2b=2b+6 | | Y=17-4y-2 | | x/4=5/12-6-x/15 | | -3v+6v=-20-1 | | 1/4(20d-16)=5d-4 | | -9+11=6x-8x | | X=21/5/8 | | 1/3(6-3a)=6 | | (2/(16x^2-4))-(2/(8x^2-8x-6)) | | 45-15=5(x-6) | | (3n+1)(n+3)+5=40 | | 7^-3/x^-2 | | 7q-13=3q+3 | | -4+3(-6n-1)=-2(-4n+5)-2 | | 5x+7.5= | | 30x-12=12x-6 | | 4y=-3.8 | | .35+3x=.45+2x | | -2y+6+3y=6 | | 5x+7(-x-10)=-82 | | 5-a=18 | | X^2-120x+3276=0 | | 4(11x-3)=-1 | | .35+3x=45+2x | | 4q+z=-9 | | -7x-4x=66 | | 3x-4=3x-5 | | 30v^3+25v^2-105v=0 | | -1/3y=11 |

Equations solver categories